Atomic-scale Element and Isotopic Investigation of 25Mg-rich Stardust from an H-burning Supernova - N. D. Nevill; P. A. Bland; D. W. Saxey; W. D. A. Rickard; P. Guagliardo; N. E. Timms; L. V. Forman; L. Daly; S. M. Reddy (The Astrophysical Journal, 2024)
We have discovered a presolar olivine from ALH 77307 with the highest ^25 Mg isotopic composition measured in a silicate to date ( δ ^25 Mg = 3025.1‰ ± 38.3‰). Its isotopic compositions challenge current stellar models, with modeling of magnesium, silicon, and oxygen showing a closest match to formation in a supernova (SN) where hydrogen ingestion occurred in the pre-SN phase. Presolar grains within primitive astromaterials retain records of processes and environmental changes throughout stellar evolution. However, accessing these records has proved challenging due to the average grain size (∼150 nm) of presolar silicates, their sensitivity to extraction agents, and instrumental restrictions, limiting the range of isotopic and chemical signatures which can be studied per grain volume. Here, we present the first known detailed geochemical study of a presolar silicate from a hydrogen-burning SN, studied in 3D without contributions to the analysis volume and at unprecedented spatial resolutions (<1 nm), essential for constraining physical and chemical processes occurring within this recently proposed stellar environment. From our results, we infer either (i) condensation within an environment depleted of heavy elements compatible with the olivine lattice under the pressure and temperature conditions during condensation, or (ii) during periods of limited mixing either near the end of the pre-SN phase or from a collapse so rapid localized pockets of different gas compositions formed.